Improving Students' Ability to Solve Space Building Problems Through the Bamboo Dancing Learning Model in Elementary School (Journal of Basic Education Research, 2024)
Purpose of the study: This study aimed to investigate the effectiveness of the bamboo dancing learning model in enhancing students' problem-solving skills related to spatial geometry. Methodology: Conducted as Classroom Action Research (CAR), the study was implemented in two cycles, each consisting of four stages: planning, action, observation, and reflection. Data collection methods included observation, tests, and documentation. The subjects were 24 students from VD class at SDN No.13/1 Muara Bulian, comprising 12 female and 12 male students. Main Findings: The study found that the bamboo dancing learning model significantly improved students' problem-solving abilities in spatial geometry. This model involved students working on problems through discussions with partners, followed by a rotation to new partners, mimicking the movements of bamboo dancing. Varied learning media were used in each cycle to enhance the learning process. In the first cycle, the success rate of students' problem-solving abilities was 61.01%, categorized as sufficient. By the second cycle, the success rate increased to 81.64%, categorized as good. These results indicate that the bamboo dancing learning model met the research achievement indicators, demonstrating its effectiveness in improving students' spatial problem-solving skills. Novelty/Originality of this study: This research is innovative as it combines spatial mathematics with the performing art of bamboo dancing. This interdisciplinary approach not only enhances students' geometric problem-solving skills but also enriches their learning experiences by integrating physical movement and cultural elements. By visualizing and physically practicing spatial concepts through bamboo dancing, students internalize the material more effectively.